The controlled synthesis of complex hollow nanostructures and prospective applications†. (10th April 2019) - Soares, Sofia F.; Fernandes, Tiago; Daniel-da-Silva, Ana L.; Trindade, Tito
Abstract : Functionality in nanoengineered materials has been usually explored on structural and chemical compositional aspects of matter that exist in such solid materials. It is well known that the absence of solid matter is also relevant and the existence of voids confined in the nanostructure of certain particles is no exception. Indeed, over the past decades, there has been great interest in exploring hollow nanostructured materials that besides the properties recognized in the dense particles also provide empty spaces, in the sense of condensed matter absence, as an additional functionality to be explored. As such, the chemical synthesis of hollow nanostructures has been driven not only for tailoring the size and shape of particles with well-defined chemical composition, but also to achieve control on the type of hollowness that characterize such materials. This review describes the state of the art on late developments concerning the chemical synthesis of hollow nanostructures, providing a number of examples of materials obtained by distinct strategies. It will be apparent by reading this progress report that the absence of solid matter determines the functionality of hollow nanomaterials for several technological applications.